UEQ-BASED EVALUATION OF USER EXPERIENCE: A CASE STUDY ON ENGLISH READING WEBSITES DEVELOPMENT - Argo Wibowo; Lemmuela Alvita Kurniawati; Susanti Malasari; Paulina Besty Fortinasari (LPPM Nusa Mandiri, 2025)
Technology has become essential in education, requiring specialized instructional media tailored to each subject. This study develops a web-based learning system designed specifically for English education, integrating both passive and interactive learning approaches to enhance engagement and effectiveness. This study contributes to showing that passive-interactive English learning websites can help users in both the advanced and non-advanced categories. However, before the system is publicly accessible, system testing focusing on user experience is important to achieve the intended learning objectives. The current study employed the User Experience Questionnaire (UEQ) framework, consisting of 26 questions across the categories of Attractiveness, Pragmatic, and Hedonic. The UEQ framework has been well-validated and widely used in various studies and professional industries for assessing user experience, ensuring that the user experience scores are objective. The findings showed that the system scored lowest in the “Hedonic” category due to a low “Novelty” score of 1.344, which was 31% lower than the highest score “Attractiveness” at 1.962. Interface that visually appealing and offers fresh, dynamic content, users are more likely to stay engaged. However, the overall average score across the three UEQ categories for the English learning system was 1.823, indicating a good user experience.